2019
DOI: 10.1038/s41598-018-38428-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cholecystectomy in Choledocholithiasis Patients Underwent Endoscopic Retrograde Cholangiopancreatography

Abstract: There are no clinical guidelines for the timing of cholecystectomy (CCY) after performing therapeutic endoscopic retrograde cholangiopancreatography (ERCP) for choledocholithiasis. We tried to analyze the clinical practice patterns, medical expenses, and subsequent outcomes between the early CCY, delayed CCY, and no CCY groups of patients. 1827 choledocholithiasis patients who underwent therapeutic ERCP were selected from the nationwide population databases of two million random samples. These patients were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
(26 reference statements)
1
29
0
Order By: Relevance
“…The worst period, when looking at the same variables, is 4 to 30 days after ERCP. (9,10) ❚ CONCLUSION…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The worst period, when looking at the same variables, is 4 to 30 days after ERCP. (9,10) ❚ CONCLUSION…”
Section: Discussionmentioning
confidence: 99%
“…Lower-risk patients can undergo laparoscopic cholecystectomy with cholangiography and laparoscopic exploration of the common bile duct, depending on the surgeon's skills and the equipment available at the hospital. (7)(8)(9)(10)(11)(12) Usually, if choledocholithiasis is identified but not removed during cholecystectomy, a subsequent ERCP is required for extraction of the stones. (13,14) Cholecystectomy must be performed safely, and inflammation resulting from the disease itself and manipulation during ERCP can hinder the surgery, increasing the operative time, the risk of bleeding and the conversion rate when compared with elective cholecystectomy without previous ERCP.…”
Section: ❚ Introductionmentioning
confidence: 99%
“…Although previous studies have shown differing results regarding cholecystectomy (CCY) due to cholelithiasis and subsequent ICC[ 32 ] or extra-hepatic cholangio-carcinoma[ 33 , 34 ], our prior study revealed that cholelithiasis patients who undergo endoscopic sphincterotomy/endoscopic papillary balloon dilatation (ES/EPBD) are at a greater risk for subsequent cholangiocarcinoma, while cholelithiasis patients who undergo CCY have reduced risk for subsequent cholangiocarcinoma[ 3 ]. These results can be explained by different inflammation sites or by CCY reducing recurrent biliary events (RBEs)[ 35 ] and further decreasing future cholangiocarcinoma rates.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, early CCY is a better choice than delayed CCY regarding hospital stay and medical expenses for treatment in some studies [14]. Still some references show that delayed CCY has a higher proportion of laparoscopy intervention [15] and a lower complication rate [16]. Although CCY is the only de nitive therapy for acute cholecystitis [4,9,17], there are patients with high short-term comorbidity risk for surgery.…”
Section: Introductionmentioning
confidence: 99%